Stress corrosion cracking susceptibility of armour layers in CO2 annulus environments – SSRT experimental simulation. (September 2022) - Ponciano Gomes, J.A.C.; Silva, S.C.; Campos, T.
Highlights: Flexible wire steel is more susceptible to CO2 stress corrosion cracking in lower temperature and higher pCO2. Higher temperature favours iron carbonate precipitation. Localized corrosion is expected at higher temperature in both pCO2 and in lower temperature in higher pCO2. The loss of mechanical properties of flexible wire steel is related to delamination process. SSRT is a fast and efficient method to assess the environment assisted cracking susceptibility of armour wires. Abstract: Flexible wires present wet occluded spaces where corrosion induces supersaturation of ferrous ions and precipitation of FeCO3 . Localized corrosion is possible due to discontinuities of the precipitated FeCO3 . This work aims to investigate the Stress Corrosion Cracking susceptibility of armour layer in FeCO3 supersaturated seawater, addressing the influence of CO2 partial pressure and strain rate, at 25 °C and at 40 °C, using the Slow Strain Rate Test. The results were expressed by ASTM G129 standard parameters. The material showed loss of ductility under all experimental conditions. The most aggressive conditions were at 25 °C, 10 bar, under 10 -7 s −1 and 10 -6 s -1 strain rates, respectively. The results showed that fracture mechanism is related to hydrogen embrittlement, suggested by the presence of internal secondary cracks on the fracture surface. These secondary cracks suggest the interference of delamination. From the results it was possible to rank the severity of experimental conditions imposed.